Habituation as an adaptive shift in response strategy mediated by neuropeptides - Evan L. Ardiel (Nature Portfolio, 2017)
Habituation is more than learning to ignore The long held notion that habituation is simply learning to ignore a repeated stimulus has been challenged by this work showing that habituation reflects a shift in response strategy to escape a repeated aversive stimulus. The laboratory of Dr. Catharine Rankin at the University of British Columbia used a microscopic roundworm (C. elegans) to investigate habituation to aversive stimuli in an attempt to understand why an animal would decrease responding to something potentially dangerous. Using computer vision software for detailed behavioral analyses, they found that for C. elegans, habituation is part of a behavioral strategy to disperse to safety away from the site of stimulation. Through a genetic analysis they identified a key signaling system underlying this process. This work reframes the purpose of habituation and begins to reveal underlying cellular and circuit processes